Investigations regarding the role of NOS1AP in the heart using a conditional overexpression mouse model. (14th October 2021) - Jaensch, M; Trum, M; Williams, T; Schmitt, J; Schuh, K; Qadri, F; Maier, L; Bader, M; Ritter, O
Abstract: Background: 35.3% of deaths in 2019 in Germany are caused by cardiovascular diseases (Destatis). 95% of these people were 60 years and older. To increase survival rate in elderly patients we investigate the relevance of altered expression of neuronal nitric oxide synthase 1 (NOS1) adaptor protein (NOS1AP) acting as an L-type calcium channel (CaV1.2) modulator via directing NOS1 to CaV1.2 on cardiac electrophysiology. Genome-wide association studies have linked genetic polymorphisms in NOS1AP to variations in QT interval duration (QTc). The QT interval reflects ventricular de- and repolarization. It may predispose individuals to ventricular tachycardia and sudden cardiac death (SCD) if prolonged, shortened or otherwise unregularly. In addition, about 20% of families with a clinically proven diagnosis of long QT syndrome (LQTS) host no mutation in any of the 16 associated genes. Methods and results: Transgenic mice with conditional overexpression of NOS1AP in cardiac myocytes were used as model organism. We confirmed the interaction of NOS1AP with NOS1 and CaV1.2. Electrocardiography in NOS1AP overexpressing mice showed atrial and ventricular tachycardia both spontaneously and upon programmed stimulation associated with a significant decrease in QTc. Heart rates in NOS1AP overexpressing mice were similar to non-induced animals. Survival was significantly reduced (only 60% after 12 weeks vs. 100% in non-induced mice). Induced QTc alterations and accompanied deaths subsided upon re-administration of doxycycline. Whole-cell patch-clamp measurements in isolated adult ventricular myocytes were performed and action potential duration at 90% of repolarization (APD90) was significantly reduced in induced transgenic NOS1AP overexpressing mice compared to control littermates. In addition, we investigated the functional effect of the human SNP rs16847548 (T/C) located within the NOS1AP promoter. The SNP was found to decrease the transcriptional activity of NOS1AP in vitro and therefore, potentially leading to a decrease in NOS1AP expression in humans. Conclusion: Myocardial overexpression of NOS1AP leads to short QT syndrome with increased susceptibility to atrial and ventricular arrhythmias and cardiac death. In accordance, APD90 is significantly shortened in overexpressing animals. The human SNP rs16847548, which is located in the promoter region of NOS1AP, results in a reduced NOS1AP promoter activity in vitro, hereby providing an explanation for the frequently published elongation of QT intervals. In summary, not only mutations in ion channels themselves but also genetic alterations in the expression of ion channel modulators such as NOS1AP, have an impact on QTc and arrhythmogenesis and represent a promising therapeutic target for LQTS patients. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Gesundheitscampus Brandenburg (MWFK)